Synergy of reduced gypsum and pressmud – a cost effective approach for sustainable reclamation of degraded sodic lands - SINGH, YASH PAL; MISHRA, VINAY K; BHARADWAJ, AJAY K; ARORA, SANJAY; SINGH, ATUL K; SINGH, SUDHANSHU; SINGH, U S; ISMAIL, A M; HAEFELE, S M (The Indian Journal of Agricultural Sciences, 2019)
The effect of improved practice [IP; gypsum application @ 25% gypsum requirement (GR) +10 t/ha press mud] over existing practice (EP; gypsum application @ 50% GR) on rice productivity and profitability in sodic soils (pH 9.2-10.4) was evaluated at farmers' fields for 3 years during 2011-14 in Hardoi district of Uttar Pradesh, India. All growth parameters were significantly higher for IP than EP, with 36.5 and 39.3% higher straw and grain yield, respectively. Interaction effect between sodicity levels and reclamation practices were significant for grain and straw yields. Use of IP with S1, S2, S3, and S4 sodicity levels reduced reclamation costs by ` 15480, 18540, 22560 and 24780/ha, respectively. The combination of reduced costs and increased yields in the IP reclamation treatment led to higher returns from rice cultivation in sodic soils, because IP effect on rice yield was better at higher sodicity level, whereas under EP, this was achieved only for sodicity levels of S2 and S3. Soil properties like pH, EC, organic carbon, exchangeable sodium percentage (ESP), contents of cations and anions were improved significantly under IP than EP. Overall, improved practice of sodic soil reclamation had better effects on soil properties and crop yields than the current practices in vogue besides considerable reduction in cost of reclamation.